Just in Time? A Temporal Analysis of the Initiation of Legislation in Coalition Governments - Kento Ohara; Matthew Hepplewhite (Institute for Replication (I4R), 2024)
In this paper, we explore the reproducibility of the König et al. (2022) paper on the timing of bill initiation under coalition governments and validate its scope condition by expanding the analysis to an additional government and country, namely the United Kingdom's Conservative-Liberal Democrat coalition government of 2010 to 2015. We find that König et al. (2022)'s main analysis is robust to reproduction, and that König et al. (2022)'s results do not travel to the UK's typical majoritarian system. Our additional contribution also highlights the potential for future research to further address the endogeneity of legislative institutions to coalition governance, and possible institutional confounders to coalition policing.
Keywords: 330; replication; reproduction; coalition government; Western Europe; Britain; Conservative-Liberal Democrat coalition; circular regression